Unpacking Stages of Mobile-Assisted Language Learning Adoption: A Narrative Inquiry - Mahardika, Anak Agung Ngurah Yudha Martin; Rahmajanti, Sri; Suwastini, Ni Komang Arie (Journal of Education Technology, 2023)
Technological advancements necessitate adaptation in the field of education, particularly for language teachers. This need cannot simply be accommodated in the classroom. In the process of adopting technology, teachers experience various processes that must be got through. This current study was aimed at filling the gap in the issues related to the complexity of MALL adoption in higher education. To fill the need for descriptive richness and picture the entire adoption process, a qualitative approach was used; specifically, Narrative Inquiry (NI). There was a total of three people who participated in the research. Data was gathered through the use of a narrative frame, an empty box, and a structured interview guide. The study's findings highlight the simultaneous and ongoing nature of the adoption process. Three distinct phases of adoption were identified by this research: acceptance (before use), usage (during use), and confirmation (after use), with three distinct evaluation procedures for each phase. Another important finding is that intention is not necessarily a drive to usage. There is review process that bridges the intention and usage. The process of intention and review are simultaneous. Nevertheless, whereas intention is likely immediate, the review takes longer period of decision making. The review process could be the answer to the debate in TAM studies related to the reasons of inconsistency of the intention to use to the usage.